The Effect of Educational Intervention on Knowledge and Attitudes toward Sexually Transmitted Infections on a Sample of Egyptian Women at Primary Care Level - Amin, Tarek Tawfik; Galal, Yasmine Samir; Shaheen , Dina Samy; Salem, Marwa Rshad (Open Access Macedonian Journal of Medical Sciences, 2021)
OBJECTIVES: The current study was conducted to assess the effect of an educational intervention on knowledge status and attitudes toward sexually transmitted infections (STIs) in a sample of women in reproductive age. METHODS: One group quasi-experimental study was conducted at one primary health care center in Egypt; included 200 women selected by systematic sampling method. Health education intervention was designed and implemented to fill the knowledge gap revealed in pre-test in relation to prevention, early detection and STIs treatment. RESULTS: The results revealed that knowledge about types, modes of transmission and causative agents of STIs, symptoms and complications of STIs, and prevention and treatment increased in post-test (p = 0.001), with significant increase of total knowledge score in post-test (p = 0.001). The attitudes toward STIs were also improved at post-test compared to pre-test. CONCLUSION: The study reflected the need for implementing educational programs to improve STIs’ knowledge and increasing women’s readiness for STIs screening.